2022
DOI: 10.1155/2022/2432309
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Machine Learning and Information Coverage Centralized Genetic Method in Safety Management of Football Training

Abstract: In recent years, China’s competitive sports have developed rapidly. Among them, football is a sport with high energy consumption, high intensity, strong antagonism, and high speed. As a result, injuries are common in football practice. It is impossible to do adequate football training in order to avoid such incidents. At the moment, football injury incidents are common, severely limiting the full growth of the sport in China. This work investigates the safety management of football training using machine learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%